2013
DOI: 10.1371/journal.pone.0067836
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Oral Active Vitamin D Is Associated with Decreased Risk of Peritonitis and Improved Survival in Patients on Peritoneal Dialysis

Abstract: Peritonitis is a major complication of peritoneal dialysis (PD) being associated with hospitalization, catheter loss, technique failure, and increased mortality. Data on incidence rates and risk factors for peritonitis episodes vary between centers. In seven Austrian PD units clinical and laboratory data on each peritonitis episode were collected from all patients (n = 726) who performed PD between January 2000 and December 2009. The peritonitis incidence rate was 0.32 episodes/patient-year. In a multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
2
21
1
1
Order By: Relevance
“…Moreover, peritonitis could have occurred independently of CKD-MBD, as our study cohort consisted of elderly patients with multiple comorbidities and a high prevalence of diabetes mellitus. (20,21) Although there have been recent reports that active vitamin D use was associated with a significant reduction in the risk of peritonitis (22,23) and longer duration of the first episode of peritonitis, (23) we did not observe any significant differences in the proportion of patients with or without peritonitis with respect to active vitamin D replacement (p = 0.85) or the type of phosphate binders administered (p = 0.83) in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…Moreover, peritonitis could have occurred independently of CKD-MBD, as our study cohort consisted of elderly patients with multiple comorbidities and a high prevalence of diabetes mellitus. (20,21) Although there have been recent reports that active vitamin D use was associated with a significant reduction in the risk of peritonitis (22,23) and longer duration of the first episode of peritonitis, (23) we did not observe any significant differences in the proportion of patients with or without peritonitis with respect to active vitamin D replacement (p = 0.85) or the type of phosphate binders administered (p = 0.83) in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…However, recent study in PD patients did not detect any benefit from paricalcitol supplementation in preventing peritoneal remodeling. In contrast to these results, Kerschbaum et al demonstrated protective effect of oral active VD against peritonitis in PD patients [33,54,76].…”
Section: Anemia and Peritoneal Fibrosismentioning
confidence: 81%
“…Interventional studies also demonstrated the decreased risk for infection in dialysis patients. VD supplementation reduced significantly the risk for hospitalization due to acute respiratory infections in hemodialysis (HD) patients; in another study, VD supplementation decreased the risk for peritonitis in patients on peritoneal dialysis (PD) [53,54]. A more recent study also demonstrated decrease in infection rates in dialysis patients treated with VDR analogs [55].…”
Section: Vd and Infectionmentioning
confidence: 99%
“…Nevertheless, mineral and bone disorders can have an impact, especially when uremic pruritus [27] or fractures weigh in, causing touch contamination and unqualified PD performance. Kerschbaum et al [28] reported that oral administration of active vitamin D is associated with a lower risk of peritonitis and according to a recent meta-analysis, the use of vitamin D in long-term dialysis patients appears to be associated with lower risk of infection-related outcomes [29]. The effect of educational attainment on peritonitis risk has been discussed in several studies; lower educational level and lower socioeconomic status [3,6,17,14] are associated with higher peritonitis rates.…”
Section: Discussionmentioning
confidence: 99%